2017
DOI: 10.1037/pspi0000094
|View full text |Cite
|
Sign up to set email alerts
|

Word order denotes relevance differences: The case of conjoined phrases with lexical gender.

Abstract: This work explores the order of linguistic references to the two genders (e.g., men and women vs. women and men). It argues that a gender is more likely to be mentioned first when it is perceived to have higher relevance in a context rather than lower relevance, and audiences assign stronger relevance to a party when the party is mentioned first rather than second.Studies 1-3 document the current prevalence of male-first conjoined phrases in the public (but not family) domain and link the pattern to historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 65 publications
0
26
0
2
Order By: Relevance
“…There are different ways that this can happen. For example, at a syntactic level, word order may signal to readers or listeners specific semantic and societal hierarchies (e.g., Hegarty et al, 2016; Kesebir, 2017). Referring to a woman and a man or to a man and a woman is not perceived as being the same, and the resulting biased representations – toward the first person mentioned – have been well documented (Hegarty et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are different ways that this can happen. For example, at a syntactic level, word order may signal to readers or listeners specific semantic and societal hierarchies (e.g., Hegarty et al, 2016; Kesebir, 2017). Referring to a woman and a man or to a man and a woman is not perceived as being the same, and the resulting biased representations – toward the first person mentioned – have been well documented (Hegarty et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Direct studies of this tendency (Carnaghi, Piccoli, Brambilla, & Bianchi, 2014;Hegarty, Watson, Fletcher, & McQueen, 2011;Kesebir, 2017) found that when participants were presented with a printed list of pairs of gender stereotyped occupations (e.g. "hairwasher-welder" or "welderhairwasher") and had to indicate whether they preferred the male-female order or the female-male mirror order, most participants preferred the male-female order, regardless of whether the occupations differed in status.…”
Section: A Subject-independent Prominent Gender Bias?mentioning
confidence: 99%
“…"hairwasher-welder" or "welderhairwasher") and had to indicate whether they preferred the male-female order or the female-male mirror order, most participants preferred the male-female order, regardless of whether the occupations differed in status. Such findings have been used to argue that word order is a means of expressing and perpetuating gender stereotypes (Kesebir, 2017).…”
Section: A Subject-independent Prominent Gender Bias?mentioning
confidence: 99%
“…In such a way aesthetic images are simulated, which can be called generalized (or typed, synthetic) due to the nature of their creation. Their development and interaction form the structure of a novel (Kesebir, 2017). The aesthetic images are formed on the basis of verbal (pronounced by speech forms, models or patterns) images which are localized within a context of the novel (Kalmykova & Kalmykov, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Psycholinguists pay considerable attention to a form of a novel, that, in their opinion, signifi cantly infl uences the reader's understanding of the text. A deep analysis of the views of scientists on the features of adequate understanding of novels we fi nd in a lot of scientifi c articles (Kesebir, 2017;Rubskyi, 2019).…”
Section: Introductionmentioning
confidence: 99%